Strength of Dry and Wet Quartz in the Low‐Temperature Plasticity Regime: Insights From Nanoindentation. Issue 2 (27th January 2022) - Ceccato, Alberto; Menegon, Luca; Hansen, Lars N.
Abstract: At low‐temperature and high‐stress conditions, quartz deformation is controlled by the kinetics of dislocation glide, that is, low‐temperature plasticity (LTP). To investigate the relationship between intracrystalline H2 O content and the yield strength of quartz LTP, we have integrated spherical and Berkovich nanoindentation tests at room temperature on natural quartz with electron backscatter diffraction and secondary‐ion mass spectrometry measurements of intracrystalline H2 O content. Dry (<20 wt ppm H2 O) and wet (20–100 wt ppm H2 O) crystals exhibit comparable indentation hardness. Quartz yield strength, which is proportional to indentation hardness, seems to be unaffected by the intracrystalline H2 O content when deformed under room temperature, high‐stress conditions. Pre‐indentation intracrystalline microstructure may have provided a high density of dislocation sources, influencing the first increments of low‐temperature plastic strains. Our results have implications for fault strength at the frictional‐viscous transition and during transient deformation by LTP, such as seismogenic loading and post‐seismic creep. Plain Language Summary: Natural quartz generally contains small amounts of water within its crystal structure. These small amounts may dramatically decrease quartz strength at high temperatures typical of the deeper portions of Earth's crust. At lower temperatures (200–300°C), the effects of these small amount of water on quartz strength is still a matter of debate. Here, we present the results of mechanical tests measuring the resistance to the penetration by a microscopic diamond tip of natural quartz grains containing different amounts of water. These experiments are expected to promote the activation of deformation mechanisms experienced by quartz in the portions of Earth's crust at intermediate depths. The results demonstrate that the mechanical resistance (i.e., strength) of quartz is similar for different intracrystalline water content. Thus, the small amounts of water contained in the quartz crystal structure do not affect its strength for this particular deformation mechanism. In addition, it seems that the high density of defects in the crystal structure, which developed during the long geological history of natural quartz samples, may control the strength of quartz just as it begins deforming in our experiments, and, by extrapolation, at intermediate depth in Earth's crust. Key Points: Low‐temperature plasticity in quartz with varying intracrystalline H2 O was investigated by spherical and Berkovich nanoindentation Naturally deformed, wet and dry quartz grains exhibit similar yield and post‐yield hardness during nanoindentation at room temperature Intracrystalline H2 O content does not affect the strength of quartz in the low‐temperature plasticity regime